Biodegradable Zn-Cu-Fe Alloy as a Promising Material for Craniomaxillofacial Implants: An in vitro Investigation into Degradation Behavior, Cytotoxicity, and Hemocompatibility - Xu, Yan; Xu, Yichen; Zhang, Wentai; Li, Ming; Wendel, Hans-Peter; Geis-Gerstorfer, Jürgen; Li, Ping; Wan, Guojiang; Xu, Shulan; Hu, Tao (Frontiers in Chemistry, 2022)
Zinc-based nanoparticles, nanoscale metal frameworks and metals have been considered as biocompatible materials for bone tissue engineering. Among them, zinc-based metals are recognized as promising biodegradable materials thanks to their moderate degradation rate ranging between magnesium and iron. Nonetheless, materials’ biodegradability and the related biological response depend on the specific implant site. The present study evaluated the biodegradability, cytocompatibility, and hemocompatibility of a hot-extruded zinc-copper-iron (Zn-Cu-Fe) alloy as a potential biomaterial for craniomaxillofacial implants. Firstly, the effect of fetal bovine serum (FBS) on in vitro degradation behavior was evaluated. Furthermore, an extract test was used to evaluate the cytotoxicity of the alloy. Also, the hemocompatibility evaluation was carried out by a modified Chandler-Loop model. The results showed decreased degradation rates of the Zn-Cu-Fe alloy after incorporating FBS into the medium. Also, the alloy exhibited acceptable toxicity towards RAW264.7, HUVEC, and MC3T3-E1 cells. Regarding hemocompatibility, the alloy did not significantly alter erythrocyte, platelet, and leukocyte counts, while the coagulation and complement systems were activated. This study demonstrated the predictable in vitro degradation behavior, acceptable cytotoxicity, and appropriate hemocompatibility of Zn-Cu-Fe alloy; therefore, it might be a candidate biomaterial for craniomaxillofacial implants.